Management of Distal Humerus Fractures With Jess Fixator - Kandel, Prakriti Raj; Shrestha, Kishor Man; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2015)
INTRODUCTION: Fractures of distal humerus are rare comprising approximately 2% of all fractures and a third of all humerus fractures. Even with the development of newer fixation techniques, the treatment of distal humerus fractures remains a great challenge to any orthopaedic surgeon. Thus this present study was conducted to evaluate the results of Joshi's External Stabilization System (JESS) in the management of distal humerus fracture with or without intercondylar extension. MATERIALS AND METHODS: This retrospective study was conducted by collecting records of thirty two adult patients who sustained distal humerus fracture and were managed with JESS fixation under anaesthesia over a period of two years in Universal College of Medical Sciences Teaching Hospital (UCMSTH) after obtaining permission from Institutional ethical committee. RESULTS: According to AO (Arbeitsgemeinschaft für Osteosynthesefragen) classification, 2 patients had C1 fracture and 30 patients had C2 fractures. The mean duration of JESS application was 16 weeks. The mean follow up was 8 months. The functional outcome was evaluated by using Cassebaum's functional rating system. Among C1 fractures, 50% showed fair and 50% showed good result whereas among C2 fractures, 40% showed good, 46.66% showed fair and 13.33% showed poor results. CONCLUSIONS: JESS fixation technique represents a viable option in the management of open as well as close intercondylar fractures of the distal humerus.